Hallucination And Imagination. - Allen, Keith (Australasian Journal of Philosophy, 2015)
What are hallucinations? A common view in the philosophical literature is that hallucinations are degenerate kinds of perceptual experience. I argue instead that hallucinations are degenerate kinds of sensory imagination. As well as providing a good account of many actual cases of hallucination, the view that hallucination is a kind of imagination represents a promising account of hallucination from the perspective of a disjunctivist theory of perception like naïve realism. This is because it provides a way of giving a positive characterisation of hallucination—rather than characterising hallucinations in negative, relational, terms as mental events that are subjectively indistinguishable from veridical perceptual experiences.